MENANAMKAN NILAI KEISLAMAN PADA PERINGATAN ISRA’ DAN MI’RAJ NABI MUHAMMAD SAW DI MASJID NURUL ISLAM DESA RANUAGUNG - Taufik, Mohammad; Qoyyum, Abdil; Ropi, Muhammad Nur; Kholis, Moh. Nur; Hayat, Moh.; Solihin6, Solihin; Hidayat, Rudi (Najah: Journal of Research and Community Service, 2024)
Ranuagung Village is one of the villages located in Tiris District, Probolinggo Regency. In addition to having a very beautiful lake charming to the eye, this village is also famous for the largest production of mangosteen and duren fruits in Probolinggo. Not only about producing fruit, cultural and Islamic traditions in Ranuagung village are also varied. Starting from the tradition of tingkeban (7 months), rejeban, maulidan, selapanan, suroan, and so on. Based on the results of the above findings, the formulation of the tradition of rejeban or more commonly called isra 'mi'raj will be the main program in this study. The selection of Isra' Mi'raj as the subject of KKN-PKM assistance in Ranuagung Village, Tiris District, Probolinggo Regency is not without reason and has been mutually agreed. There is an update to the concept of activities to give a different and more attractive impression from the warnings that were previously the main focus in the mentoring process this time. This PKM activity is carried out with steps that refer to Inculturation, Discovery, Design, Define and Reflection. The activity began with the reading of the holy verses of the Qur'an by student representatives. Next is the reading of istighosah together, followed by the reading of the Prophet's mawlid and prayer. Then the next session was a short lecture regarding the important events of Isra' Mi'raj. In this case, the commemoration of Isra' Mi'raj is generally celebrated in various ways. However, for residents in rural areas, it needs renewal as well as development with the aim of better understanding the meaning of the celebration of the night of Isra' and Mi'raj.